The role of fibrinogen, fibrin and fibrin(ogen) degradation products (FDPs) in tumor progression - Kołodziejczyk, Joanna; Ponczek, Michał B. (Contemporary Oncology/Współczesna Onkologia, 2013)
Participation of fibrin, fibrinogen, and their degradation products in pathogenesis and progression of cancer may lead to complications of thromboembolic events. The tumor may be a source of fibrinogen. Fibrinogen inside the tumor is one of the factors of its growth and metastasis. Fibrinogen, fibrin and their degradation products possess proinflammatory activity. They indirectly stimulate endothelium to secrete von Willebrand factor, leading to activation of platelets accompanying neoplastic disorders. Fragments E and D are the end products of fibrin(ogen) degradation and E and DD are the end products of stabilized fibrin. E stimulates proliferation, migration and differentiation of endothelial cells, contributing to tumor vasculature. Increased levels of DD are observed in malignant neoplasms, such as breast, lung, colon and ovary cancers. In breast cancers DD correlates with progression of disease and metastasis. The role of fibrinogen and the products of its degradation in the progression of various tumors is not sufficiently understood.